The Effect of Dengue Haemorrhagic Fever Education on the Knowledge of Elementary School Students - Cornelia Dede Yoshima Nekada; Chelsy Rambu Leki Tuga; Tia Amestiasih (Indonesian Journal of Global Health Research, 2023)
Indonesia is a tropical country, with one typical endemic disease, dengue fever (DHF). This infectious disease occurs due to the bite of Aedes Aegypti and Ades Albopictus mosquitoes. The Yogyakarta Health Office in 2022 explained that dengue data until November 2022 there were 2,027 cases of dengue, the number was divided in various areas of the city of Jogjakarta. Sleman is the district with the 3rd highest number of DHF cases in Yogyakarta with 289 cases. The Ministry of Health (2023) explained that until the fourth week, the number of dengue cases in Indonesia reached around 710 cases starting in 2023. To determine the effect of dengue fever education on students' knowledge. This type of research is quantitative research with quasi quasi-experimental design pre and post-test without a control group. The sampling technique used in this study was total sampling with a sample size of 76 students at SD Negri Pokoh 1. The research instrument used was a questionnaire about the level of knowledge of dengue fever. This research instrument was tested for validity and reliability with expert judgement and obtained a value of 0.925. The statistical test used was the Wilcoxon test. This study showed that most of the respondents were male out of 76 students at Pokoh 1 Elementary School. The average value of students' knowledge about Dengue Fever before education is 71.78. The average value of students' knowledge after Dengue Fever education is 83.36. There is an effect of Dengue Fever education on the knowledge of Pokoh 1 Elementary School students.